Association between Secondhand Smoke Exposure and Metabolic Syndrome in 118,609 Korean Never Smokers Verified by Self-Reported Questionnaire and Urine Cotinine - Kim, Ji Hye (Endocrinol Metab (Seoul), 2020)
BACKGROUND: No study has reported the association between secondhand smoke (SHS) exposure and metabolic syndrome (MetS) in self-reported never smokers verified by both self-reported questionnaire and urine cotinine. METHODS: A total of 118,609 self-reported and cotinine-verified never smokers (38,385 male; age 34.8±7.1 years) who participated in the Kangbuk Samsung Health Study between 2011 and 2016 were included. Cotinine-verified never smokers were defined as individuals with urinary cotinine <50 ng/mL. SHS exposure was defined as current exposure to passive smoking indoors at home or workplace. RESULTS: Prevalence of SHS exposure in the overall population was 22.6% (27.4% for males and 20.3% for females (P<0.001). The overall prevalence of MetS was 6.8% and was higher in males than in females (10.7% vs. 4.9%, P<0.001). In both genders, MetS prevalence was higher in the SHS exposure group than the non-SHS exposure group (11.3% vs. 10.4%, P=0.010 for males; 5.8% vs. 4.6%, P<0.001 for females). However, there was significant gender interaction for the association between SHS exposure and MetS (P for interaction=0.010). In the multivariate regression analyses, SHS exposure was associated with increased MetS odds only in females (odds ratio [95% confidence interval], 1.02 [0.94 to 1.11] in male vs. 1.17 [1.06 to 1.29] in female). In particular, females with SHS exposure of ≥1 hour/day and ≥3 times showed increased odds of MetS compared with those without SHS exposure (1.22 [1.02 to 1.45], 1.30 [1.14 to 1.49]). CONCLUSION: This cross-sectional study showed that SHS exposure was significantly associated with prevalence of MetS in self-reported and cotinine-verified female never smokers.